The protection of waters in agricultural production in the light of new challenges - Puślecki, Damian (Przegląd Prawa Rolnego, 2023)
The aim of the considerations was to assess the legal regulation of water protection in the process of agricultural production from the perspective of the Common Agricultural Policy 2023-2027. It has been established that the current regulation does not provide for adequate water protection due to, primarily, its fragmentation, weak impact on the protection of water resources and unsatisfactory sanctions currently available for polluting this element of the environment. The challenges arising from the Common Agricultural Policy are capable of influencing the improvement of the existing situation but the protection of waters in agricultural production requires constructing a legal regulation based on properly balanced preventive and incentive instruments. The legal regulation needs to be systematised taking into account the issues of food security, the preservation of the productive capacity of agriculture and the rational use of water, soil and air in the agricultural production process.